-1
$\begingroup$

I need to calculate the probability distribution (p.m.f.) of $X=X_1X_2 \cdot \cdot \cdot X_n$ where $X_i \in \{1,2\}$ and $X_i$ are iid with probabilities $p$ and $1-p$ respectively.

Since $X=2^n$ for $n \in\mathbb{N}$, then rather than inferring the distribution directly, one could consider $\log_2(X)=log_2(X_1)+log_2(X_2)+ \cdot \cdot \cdot +log_2(X_n)$ that's known to have a binomial distribution of some sort (because $X_1+ \cdot \cdot \cdot + X_n$ of bernoulli r.v.s has).

But if one infers the distribution in $log_2$ scale (and what's the p.m.f. of $\log_2(X)$?), then how do I transform back to the original scale?

$\endgroup$
  • 1
    $\begingroup$ Your question is not presented well enough. Do you want to find the pdf of $X$? Are $X_i$s iid? $\endgroup$ – msm Nov 23 '16 at 11:56
1
$\begingroup$

Let $$X=\prod_{i=1}^{n}X_i$$ So $$Z=\log_2X=\sum_{i=1}^{n}\log_2X_i$$

Define $Y_i=\log_2X_i$. It turns out $Y\sim Bernulli(1-p)$ and $Z\sim Binom(n,1-p)$. The support of $Z$ is $[0,n]$

and $$X=2^Z,\,X\in [1,2^n]$$ $$p_X(x)= p_Z(\log_2x)=\binom{n}{\log_2x}p^{n-\log_2x}(1-p)^{\log_2x}$$ where $x=2^k$. SO it can also be written as $$p_X(2^k)= p_Z(k)=\binom{n}{k}p^{n-k}(1-p)^{k}$$

$\endgroup$
0
$\begingroup$

Let $X_n$, $n=1,2,\ldots$ be i.i.d. random variables with $$\mathbb P(X_1=1) = p = 1-\mathbb P(X_1=2). $$ For each positive integer $n$, let $$Y_n = \prod_{j=1}^n X_j,$$ then $$\mathbb P(Y_1=1)=p=1-\mathbb P(Y_1=2). $$ Suppose for some integers $n,k$ such that $0\leqslant k\leqslant n$ and $n>0$, $$\mathbb P\left(Y_n = 2^k\right) = \binom nk (1-p)^kp^{n-k}. $$ Then for $0\leqslant k\leqslant n+1$ we have \begin{align} \mathbb P\left(Y_{n+1}=2^k\right) &= \mathbb P\left(X_{n+1}Y_n = 2^k\right)\\ &=\mathbb P\left(X_{n+1}Y_n = 2^k\mid X_{n+1}=1\right)\mathbb P(X_{n+1}=1)\\ &\quad+\mathbb P\left(X_{n+1}Y_n = 2^k\mid X_{n+1}=2\right)\mathbb P(X_{n+1}=2)\\ &= \mathbb P\left(Y_n=2^k\right)\mathbb P(X_{n+1}=1) + \mathbb P\left(Y_n=2^{k-1}\right)\mathbb P(X_{n+1}=2)\\ &= p\binom nk (1-p)^kp^{n-k} + (1-p)\binom n{k-1} (1-p)^{k-1}p^{n+1-k}\\ &= \left(\binom nk + \binom n{k-1}\right)(1-p)^kp^{n+1-k}\\ &= \binom {n+1}k (1-p)^kp^{n+1-k}. \end{align} It follows by induction that $\xi_n := \lg Y_n$ has $\operatorname{Bin}\left(n,1-p\right)$ distribution, that is, $$\mathbb P(\xi_n = k) = \binom nk (1-p)^kp^{n-k}. $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.